CONTINGENCY FACTORS IN MANAGEMENT ACCOUNTING PRACTICES IN MSMEs IN THE FOOD SECTOR IN CENTRAL JAVA - Khoirul Fuad; Winarsih Winarsih; Retno Tri Handayani; Zuliyati Zuliyati (Jurnal Aplikasi Akuntansi, 2023)
The Covid-19 pandemic impacts the increasing of environmental uncertainty for a business. Amid this condition, as one of the pillars of the country's economy, MSMEs must have high business quality and competitiveness. With good management accounting practices, MSME owners will have sufficient information relevant to their business. This certainly impacts the higher and more valid decisions taken by managers or business owners. Therefore, it is essential to investigate what contingency factors affect management accounting practice. The object of this study is SMEs in the food sector in Semarang. The hypothesis test used is multiple linear regression. The results of this study indicate that environmental uncertainty and information technology have a positive effect on management accounting practices. For market competition and accounting, training is not proven to significantly affect management accounting practice.